Froude, Eldon. Eldon Froude photographs - Flaherty, Sara M. (2000)
This fonds consists of two photographs and a scroll relating to Private Eldon Froude, a Newfoundland soldier who was killed in World War I. These are small threads which connect the living Eldon Froude, brother and soldier, with the dead, a name on a headstone and a piece of paper acknowledging the sacrifice he made for his country.